2000
DOI: 10.1590/s0100-84042000000400001
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and intercellular compartmentation of carbohydrate metabolism in leaves of temperate gramineae

Abstract: -This review considers the importance of compartmentation in the regulation of carbohydrate metabolism in leaves. We draw particular attention to the role of the vacuole as a site for storage of soluble sugars based on sucrose, and discuss briefly their characteristic metabolism. We also point out inconsistencies between the observed properties of vacuoles and the behaviour in vitro of the enzymes of fructan biosynthesis that do not support the hypothesis that the vacuole is the site of synthesis as well as of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In support of this aspect, several studies have provided biochemical evidence for the uptake of both Suc and hexoses into vacuoles (Thom et al, 1982;Rausch, 1991;Keller, 1992), and both passive diffusion and active transport have been determined as uptake mechanisms for these sugars (Thom and Komor, 1984;Martinoia et al, 1987Martinoia et al, , 2000. Furthermore, determination of subcellular sugar concentrations in a variety of plants via nonaqueous fractionation (Gerhardt and Heldt, 1984) revealed that in leaves, Glc is predominantly found in the vacuole, while Suc is mainly found in the cytosol or is evenly distributed (Wagner, 1979;Heineke et al, 1994;Pollock et al, 2000;Voitsekhovskaja et al, 2006).…”
mentioning
confidence: 94%
“…In support of this aspect, several studies have provided biochemical evidence for the uptake of both Suc and hexoses into vacuoles (Thom et al, 1982;Rausch, 1991;Keller, 1992), and both passive diffusion and active transport have been determined as uptake mechanisms for these sugars (Thom and Komor, 1984;Martinoia et al, 1987Martinoia et al, , 2000. Furthermore, determination of subcellular sugar concentrations in a variety of plants via nonaqueous fractionation (Gerhardt and Heldt, 1984) revealed that in leaves, Glc is predominantly found in the vacuole, while Suc is mainly found in the cytosol or is evenly distributed (Wagner, 1979;Heineke et al, 1994;Pollock et al, 2000;Voitsekhovskaja et al, 2006).…”
mentioning
confidence: 94%
“…The application of a non‐aqueous fractionation technique allowed estimates of the relative amounts of sugars in sub‐cellular compartments. Measurements of sugar concentrations in a variety of plants revealed that in leaves the vast majority of glucose is found in the vacuole [12–17] (Lohaus G., personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…Vacuoles serve as a main long-term and also temporary storage pool in the cell (i.e. metabolites produced in excess are transported into vacuoles and released according to metabolic requirements; Cairns et al, 2000;Pollock et al, 2000;Wormit et al, 2006;Martinoia et al, 2007;Neuhaus, 2007). In this process, specific tonoplast sugar transporters are required for the vacuolar transport of these nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…metabolites produced in excess are transported into vacuoles and released according to metabolic requirements; Cairns et al. , 2000; Pollock et al. , 2000; Wormit et al.…”
Section: Introductionmentioning
confidence: 99%